The transmembrane domains of the type III secretion system effector Tir are involved in its secretion and cellular activities - Braverman, Dor; Gershberg, Jenia; Sal-Man, Neta (Frontiers in Cellular and Infection Microbiology, 2023)
Enteropathogenic Escherichia coli (EPEC) is a diarrheagenic pathogen and one of the major causes of gastrointestinal illness in developing countries. EPEC, similar to many other Gram-negative bacterial pathogens, possesses essential virulence machinery called the type III secretion system (T3SS) that enables the injection of effector proteins from the bacteria into the host cytoplasm. Of these, the translocated intimin receptor (Tir) is the first effector to be injected, and its activity is essential for the formation of attaching and effacing lesions, the hallmark of EPEC colonization. Tir belongs to a unique group of transmembrane domain (TMD)-containing secreted proteins, which have two conflicting destination indications, one for bacterial membrane integration and another for protein secretion. In this study, we examined whether TMDs participate in the secretion, translocation, and function of Tir in host cells. For this purpose, we created Tir TMD variants with the original or alternative TMD sequence. Our results suggested that the C-terminal TMD of Tir (TMD2) is critical for the ability of Tir to escape integration into the bacterial membrane. However, the TMD sequence was not by itself sufficient and its effect was context-dependent. Moreover, the N-terminal TMD of Tir (TMD1) was important for the postsecretion function of Tir at the host cell. Taken together, our study further supports the hypothesis that the TMD sequences of translocated proteins encode information crucial for protein secretion and their postsecretion function.